A flexible electromagnetic wave-electricity harvester - Lv, Hualiang; Yang, Zhihong; Liu, Bo; Wu, Guanglei; Lou, Zhichao; Fei, Ben; Wu, Renbing (Nature communications, 2021)
Developing an ultimate electromagnetic (EM)-absorbing material that can not only dissipate EM energy but also convert the generated heat into electricity is highly desired but remains a significant challenge. Here, we report a hybrid Sn@C composite with a biological cell-like splitting ability to address this challenge. The composite consisting of Sn nanoparticles embedded within porous carbon would split under a cycled annealing treatment, leading to more dispersed nanoparticles with an ultrasmall size. Benefiting from an electron-transmitting but a phonon-blocking structure created by the splitting behavior, an EM wave-electricity device constructed by the optimum Sn@C composite could achieve an efficiency of EM to heat at widely used frequency region and a maximum thermoelectric figure of merit of 0.62 at 473 K, as well as a constant output voltage and power under the condition of microwave radiation. This work provides a promising solution for solving EM interference with self-powered EM devices. Materials that can harvest electromagnetic (EM) waves and harness the resulting energy would have many applications. Here, the authors present a hybrid composite that produces thermoelectricity from the heating in the EM absorption under microwave radiation.